Strengthening Preservice Teachers' Understanding of Culturally Responsive Classrooms Through Exposure, Immersion, and Dialogue - Christina L. Wilcoxen; Amanda L. Steiner; Julie Bell (The University of Alabama, 2022)
Schools around the world are incredibly diverse; therefore, understanding inclusion, equity, and social justice is an essential part of teacher preparation. Preservice teachers need guidance to identify and reflect on the personal lenses they bring to their classrooms. This reflection, in turn, helps them understand, relate to, and meet student needs. Partnerships between urban school districts, communities, and universities are necessary to strengthen preservice teachers' application of culturally responsive teaching practices. Using a mixed-methods, sequential design, the authors addressed the following research questions: In what ways, if any, does the structure of the teacher preparation program impact preservice teachers' comfort with, understanding of, and/or application of culturally responsive teaching practices in urban teaching environments? Were there specific components of the structure that supported preservice teacher development? The authors conclude by sharing a conceptual framework for structuring authentic field experiences to support culturally responsive teaching practices in preservice teachers.